Modes of protection of video data from unauthorized access - Рябова, Любов Володимирівна; Подгорний, Євгеній Іванович; Мацуева, Карина Андріївна (Ukrainian Information Security Research Journal, 2013)
The paper reviews existing methods of protection of video. A consequence of the mass distribution of video technology has become illegal copying and viewing of video data - a problem of protection of video. In particular, video data can be distributed to copyright infringement (piracy), and these may refer unauthorized competitors or hackers to obtain sensitive information (espionage). The simplest approach to the protection of video data - is die use of classical encryption schemes open or secret key. Image data file is encrypted and then transmitted over the insecure communications channel or recorded on unprotected media. This method provides a very high degree of protection of video data is achieved by a high resistance used for protection cipher. Often, however, the amount of encrypted data over the text and audio data even considerably more, which requires significant computing resources to such encryption of data. This tends to limit the possibility of using classical encryption in areas such as interactive and cable TV. Users of these services should have a powerful system capable of realtime, without delays decoding, and then decode the received data. Since the main standard used to encode and compress video data format is MPEG, then most of the methods of protection designed specifically for this format. They use features and coding structure of MPEG to reduce the computational resources to protect the video data. One way to protect the first data in the MPEG algorithm was permutation «zigzag». Its essence consists in reading the quantized coefficients of discrete cosine transform method is not «zigzag» for subsequent encoding as defined format, randomly. Different methods of protection vidiodannyh applied to telecommunications systems real-time.